CLINICAL TRIALS: PERSPECTIVES OF MEDICAL COMMUNITY - SANKAR KN, HARI; PALAPPALLIL, DHANYA SASIDHARAN; PANATTIL, PRABITHA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to determine the knowledge, attitude, and perception about clinical trials (CTs) among medical community of a tertiary care institution. Methodology: This was a questionnaire-based cross-sectional study conducted in the Department of Pharmacology, Government Medical College in Central Kerala for a period of 1 year. In a sample population of 690 comprising medical undergraduates (3rd phase), residents, and doctors in Medical Education Service (MES), 309 questionnaires were distributed randomly assuming 80% response to achieve the sample size of 247. Knowledge, attitude, and perceptions were quantified with a cumulative score with a scoring scheme of +1 for a correct response/positive attitude/positive perception and 0 for an incorrect response/no response/negative attitude/negative perception. The data were analyzed using SPSS 16, the knowledge, attitude, and perception were expressed as mean score as well as proportion. Results: The response rate was 95.79%. Of the 296 completed responses, 158 (53.4%) were from medical undergraduates, 62 (20.9%) from residents, and 76 (25.7%) from doctors in MES. The mean knowledge was 14.8±3.79 (maximum score 25). The mean attitudinal score was 7.07±1.82 (maximum score 10). The mean score of the participants on perception (maximum score=10) about CTs conducted in India was 4.11±2.02 which denoted a negative perception. Conclusion: The participants had good knowledge and positive attitude about CTs, however, all the three groups of participants had negative perception about CTs currently conducted in India.